THE EFFECT OF PROPPING ON THE PERFORMANCE OF MANUFACTURING COMPANIES IN INDONESIA - Supatmi Supatmi; Steppani Steppani (Universitas Airlangga, 2021)
This study aims to find empirical evidence of the impact of propping- related party transactions on company performance. The research sample was manufacturing companies listed on the IDX during 2017-2019 which were determined by purposive sampling and using the Generalized Least Square panel data regression analysis technique (cross-section weights). The results showed that propping (related party transactions related to account payables) had a positive effect on financial performance and had a negative effect on the company's market performance. Propping (related party transactions related to other payables) had a positive effect on the company's financial performance but doesn’t an affect on the company's market performance. Meanwhile, propping (related party transactions related to liabilities other than account payables) had a negative effect on financial performance but had a positive effect on the company's market performance.